Perbandingan Pemberian Foot Massage dengan Effleurage Massage Terhadap Nyeri Luka Operasi Sectio Caesarea (Sc) di RS Marinir Cilandak Jakarta Selatan - Anjar Restinah; Vivi Silawati; Bunga Tiara Carolin (Universitas Malahayati Lampung, 2024)
ABSTRACT Postoperative pain is still a problem in health services worldwide. One way to manage pain management is through massage, such as foot massage and effleurage massage. The results of a preliminary study on post SC at the Marine Hospital found that 90% felt moderate pain and 10% felt severe pain. To find out the comparison of giving foot massage with effleurage massage to sectio caesarea (SC) surgical wound pain at the Cilandak Marine Hospital, Jakata Selatan, in 2023. Quasy experiment with pretest-posttest design with control group design. The sample in the study was post SC mothers in May 2023 as many as 30 respondents using a purposive sampling technique. Data analysis used the paired sample t-test and Independent T-Test, which were previously tested for normality and homogeneity. The results of univariate research on surgical wound pain before and after giving foot massage decreased with a difference in mean value of 3.00, surgical wound pain before and after giving effleurage massage decreased with a difference in average value of 0.67. The results of the bivariate study were paired sample t-test foot massage (p value 0.000) and effleurage massage (p value 0.003). Independent T-Test test results with a p value of 0.000. There are differences in giving foot massage with effleurage massage for sectio caesarea surgery wound pain. It is hoped that health workers, especially midwives, can intervene in foot massage combined with effleurage massage in an effort to reduce pain levels in postoperative mothers with sectio caesarea because in addition to reducing pain levels it can also create a feeling of comfort so that it affects the physical and psychological conditions of the mother. Keywords: Foot Massage, Effleurage Massage, Sectio Caesarea Surgery Wound Pain ABSTRAK Nyeri pasca operasi masih menjadi permasalahan dalam pelayanan kesehatan di seluruh dunia. Penatalaksanaan manajemen nyeri salah satunya dilakukan dengan massage seperti foot massage dan effleurage massage. Hasil studi pendahuluan pada post SC di RS Marinir didapatkan 90% merasakan nyeri sedang dan 10% merasakan nyeri berat. Mengetahui perbandingan pemberian foot massage dengan effleurage massage terhadap nyeri luka operasi sectio caesarea (sc) di RS Marinir Cilandak Jakata Selatan Tahun 2023. Quasy experiment dengan rancangan pretest-posttest with control group design. Sampel dalam penelitian yaitu ibu post SC pada bulan Mei 2023 sebanyak 30 responden dengan teknik purposive sampling, analisa data menggunakan uji paired sample t-test dan T-Test Independent yang sebelumnya dilakukan uji normalitas dan homogenitas. Hasil penelitian univariat nyeri luka operasi sebelum dan sesudah pemberian foot massage mengalami penurunan dengan selisih nilai rata-rata 3,00, nyeri luka operasi sebelum dan sesudah pemberian effleurage massage mengalami penurunan dengan selisih nilai rata-rata sebesar 0,67. Hasil penelitian bivariat uji paired sample t-test foot massage (p value 0,000) dan effleurage massage (p value 0,003). Hasil uji T-Test Independent dengan p value 0,000. Terdapat perbedaan pemberian foot massage dengan effleurage massage terhadap nyeri luka operasi sectio caesarea. Diharapkan tenaga kesehatan khususnya bidan dapat melakukan intervensi foot massage dikombinasikan dengan effleurage massage dalam upaya penurunan tingkat nyeri pada ibu bersalin post operasi sectio caesarea karena selain dapat menurunkan tingkat nyeri juga dapat menciptakan rasa nyaman sehingga berpengaruh pada kondisi fisik maupun psikologis ibu. Kata Kunci: Foot Massage, Effleurage Massage, Nyeri Luka Operasi Sectio Caesarea